Enabling net-zero GHG emissions in the UK metals and transport industries through a circular supply chain framework - Adeyemi, Olabisi I.; Sarfraz, Shoaib; Salonitis, Konstantinos (Elsevier, 2024)
The UK metals industry is indispensable in achieving the country’s net-zero greenhouse gas (GHG) emissions target by 2050, especially considering the heavy reliance of the transport sector on metals. This paper proposes strategies based on recycling and refining locally sourced scrap metals to build a robust circular supply chain. Findings revealed that 16% of global crude steel is used in transport and this accounts for 8% of the world’s GHG emissions. Domestically, iron and steel account for 14% of the UK industrial emissions, with over 8 million metric tons of scrap metals exported annually. Insights from stakeholders revealed export dependency and infrastructure gaps impeding circularity. Collaborative efforts between industry, government, and recyclers are vital. Investing in electric arc furnaces and storage can enable the processing of domestic metal scrap for high-quality yield. A closed-loop flow of battery-critical metals will also support sustainable manufacturing of electric vehicles. Ultimately, this paper advocates systemic efforts across policy, technology, infrastructure, and partnerships to realise a sustainable supply chain in the metals industry aligned with the decarbonisation and circular economy goals.
57th CIRP Conference on Manufacturing Systems 2024, 29-31 May 2024, Póvoa de Varzim, Portugal
Keywords: 4014 Manufacturing Engineering; 40 Engineering; 12 Responsible Consumption and Production; 9 Industry, Innovation and Infrastructure; 13 Climate Action; 4014 Manufacturing engineering